68 The Incidence of Pathogenic Mutations in Index Cases of HCM, LQTS and CPVT: Results from a Clinical Testing Programme in Wales. (6th June 2015) - Anderson, Mark; Procter, Annie; McDowell, Ian; Butler, Rachel; Davies, Sally
Abstract : International guidelines suggest that a significant majority of patients with Hypertrophic Cardiomopathy (HCM), Long QT syndrome (LQTS) and Catecholaminergic Polymorphic Centricular Tachycardiac (CPVT) will be found to have a disease causing mutation on genetic testing. Until recently genetic testing was not available for patients in Wales with these conditions. From 2013 funding has been made available to test index cases to allow cascade testing of family members. We present the results of the first full year of testing. Patients with a clinical diagnosis of HCM, LQTS or CPVT in whom family cascade testing would be clinically useful were referred to one of 3 Cardiogenetics MDTs. Cases where diagnostic and family criteria were met were referred on for genetic counselling prior to testing. Samples were sent to an accredited laboratory for testing for HCM (MYH7, MYBPC3, TNNT2 and TNNI3), LQTS (KCNQ1, KCNH2, KCNE1, KCNE2 and SCN5A) or CPVT (RYR2) mutations. Results were returned to the All Wales Genetic service for collation and distribution to the patients and MDTs. In the first full year of testing (2013/2014) 75 patients were tested, 45 for HCM, 28 for LQT and 2 for CPVT. The results of testing are shown in the Figure 1 . Number of cases: Of the 45 index cases with HCM tested only 10 (22%) had a recognised pathogenic mutation whilst for LQT 8 of 28 tested had a pathogenic mutations (28%). Variants of unknown significance accounted for another 11% (HCM) and 7% (LQT) of cases. Only two cases were tested for CPVT and 1 had a pathogenic mutation (50%). Over the period of this study 47 cascade tests were performed in HCM and LQT families. Of these 30 were negative for the identified pathogenic mutation enabling these patients to be removed from clinical surveillance programmes. In this real world clinical testing programme of index cases with HCM, LQTS or CPVT, pathogenic mutation rates were substantially lower than reported in international guidelines. Away from specialist centres where large families with multiple affected members may tend to congregate pathogenic mutation rates may be lower than reported. Nonetheless cascade testing from affected families identified a significant number of individuals who could be removed from long-term clinical surveillance with potential savings in resources.